Diplomatic Correspondence: A Comparative Study on Malay and Javanese Letters in 1800s - Gilang Maulana Majid (IKAT: The Indonesian Journal of Southeast Asian Studies, 2019)
A more established tradition may set an indirect consensus for thecommunication between rulers in any situation. This article identifies howdiplomatic correspondence was conducted and how different perceptions could actually be negotiated to attain certain goals. Two diplomatic letters – one from the Panembahan of Sumenep and one from the Sultanof Yogyakarta dispatched to Thomas Stamford Raffles to address Raffles’retirement during the British interregnum in Java from 1811 to 1816 –were analyzed. These letters were chosen due to the different scripts and languages used in the two letters: Classical Malay Jawi and Old Javanese'aksara Jawa'. By applying content analysis, this study finds that the Malay language was not only influential throughout the Indonesian archipelagoas a medium for verbal communication, but its letter-writing tradition even clearly affected its Javanese counterpart, setting a standard writing style for diplomatic letters.